Answer:
Option B
Increases
Explanation:
to solve this problem, let us plug in figures to replace the variables in the equation.
Let y be equals to the rational exponent which represents the cube root of x^m,
The equation is given as y =
![\sqrt[3]{x^(m)}](https://img.qammunity.org/2021/formulas/mathematics/middle-school/2j05kmnre7ar1h2ifjrvod1x7bbdiumxw9.png)
let x= 3
and m =, 3, 4, and 5
when m = 3, we have
![y =\sqrt[3]{3^(3)} =3](https://img.qammunity.org/2021/formulas/mathematics/middle-school/shbrk0h3mkmfszook18lb470o9smhca7vj.png)
when m = 4, we have
![y =\sqrt[3]{3^(4)} =4.33](https://img.qammunity.org/2021/formulas/mathematics/middle-school/vlizrm8a9r3j3h01aousw57icsfpzec7jl.png)
when m = 5, we have
![y =\sqrt[3]{3^(5)} =6.24](https://img.qammunity.org/2021/formulas/mathematics/middle-school/nj0h9dlj7ra6smj87e5jp730t50smjsxjl.png)
As we can see, the values of y are increasing. Hence, we can say that the value of the rational exponent increases as y increases